Natural and Human-Induced Hazards and Disasters in Africa - Mulugeta, Genene (Africa Institute of South Africa, 2016)
Natural and human-induced environmental hazards are becoming increasingly prominent. The frequency of recorded natural disasters rose markedly during the last century, from about 100 per in the years up to 1940 to nearly 2 800 during the 1990s. Africa is the only continent whose share of reported disasters has increased over the past decade. Several factors contribute to Africa's high vulnerability to disasters. These include the high rate of population growth, food insecurity, high levels of poverty, inappropriate use of natural resources, and failures of policy and institutional frameworks. Despite the huge negative impact of natural and human-induced hazards on Africa's development, little is done to prevent them. Disaster prevention contributes to lasting improvement in safety and sustainable livelihoods and is essential as part of integrated disaster management strategies. The provision of effective scientific input to policy formulation on various issues related to hazards and disasters is an ambitious undertaking. It requires the collaborative effort of the African scientific community to develop comprehensive long-term strategies and human capacity-building initiatives that will enable science to benefit society.